ESTIMASI CADANGAN KLAIM PRODUK ASURANSI JIWA KREDIT UNTUK PESERTA PENSIUN - Catur Widyo Utomo; Mulawarman Awaloedin (UM. Bengkulu, 2023)
Theoretically, insurance companies rarely suffer losses. Insurance companies in managing finances, are very careful, because they will face possible risks in the future in the form of claim payments. Therefore, in selling the products, they do not use the usual forms of marketing. They use agents and brokers in distributing risk products that are sold. In addition, for certain reasons, the company also cooperates with other parties. This cooperation is essentially a form of strategic alliance. Namely cooperation between the insurance company as the issuer of the policy with the bank as the owner of credit for customers. The problem is how insurance companies face the risk of claims in the future for bank customers who have retired status and are vulnerable to the risk of death. This article discusses term loans from customers at a bank as the insured who has retired status and they are guaranteed by an insurance company as the insurer. How much funds are provided by the insurer in the future to pay the risk of death (claims) of the insured? Using the semi-continuous prospective reserve method for term life insurance products, the results show that the insurer is experiencing liquidity difficulties in order to bear the burden of claims that have already occurred and are expected to suffer losses later. The reinsurance scheme offered has also not been able to cover the insurer's losses. Therefore, the most feasible scheme to assist the insurer's liquidity due to high claims is to enlarge new policies through the scheme of entry age for the insured with a younger age while continuing to run the reinsurance scheme.